ChemInform Abstract: Chiral Phosphoric Acid Catalyzed Highly Enantioselective Friedel—Crafts Alkylation Reaction of C3‐Substituted Indoles to β, γ‐Unsaturated α‐Ketimino Esters. Issue 25 (5th June 2015) - Bi, Bo; Lou, Qin‐Xin; Ding, Yu‐Yang; Chen, Sheng‐Wei; Zhang, Sha‐Sha; Hu, Wen‐Hui; Zhao, Jun‐Ling
Abstract: The scalable reaction allows the preparation of C2‐substituted indole derivatives bearing an α‐ketimino ester motif in moderate to high yields.